Proposed Steganography Method Based on DCT Coefficients - Al-Saffar, A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this paper an algorithm for Steganography using DCT for cover image and DWT for hidden image with an embedding order key is proposed. For more security and complexity the cover image convert from RGB to YIQ, Y plane is used and divided into four equally parts and then converted to DCT domain. The four coefficient of the DWT of the hidden image are embedded into each part of cover DCT, the embedding order based on the order key of which is stored with cover in a database table in both the sender and receiver sender. Experimental results show that the proposed algorithm gets successful hiding information into the cover image. We use Microsoft Office Access 2003 database as DBMS, the hiding, extracting algorithms were implemented using MALAB R2009a.